The Improvement of the Reading Skill by Using Barron’s TOEIC Strategy for Vocational School - Umar, Umar (Academic Journal Perspective: Education, Language, and Literature, 2017)
This research aims at finding out the use of Barronâ€™s TOEIC strategy to improve the reading skill of the eleventh grade students at SMK Negeri Tinambung academic year 2010/2011.The objectives of the research were to find out whether or not the use of Barronâ€™s TOEIC preparation course package significantly improves the reading ability of the eleventh grade students at SMK Negeri Tinambung academic year 2010/2011.The research used quasi experimental research design. The samples consisted of 50 students which belonged to two groups; experimental group and control group. The research data were collected using the reading test which was given to the both groups. The research results indicated that the use of Barronâ€™s TOEIC strategyÂ did not significantly improve the reading ability of the eleventh grade students at SMK Negeri Tinambung academic year 2010/2011. The results of posttest of both groups were improved, but the use of Barronâ€™s TOEICstrategy gave better progress than handbook of vocational school namely English in Progress Business & Management for SMK Year XI: TOEIC based Activities, By Munash F. Anwar. It was proved by the mean score of posttest of the experimental group was higher than the control group in reading (85.40 > 79.20).